ANALYSIS OF CONSUMER PREFERENCES IN THE TAKENGON SYALIA HOME INDUSTRY IN BLANG KOLAK II VILLAGE, BEBESEN DISTRICT CENTRAL ACEH DISTRICT - André Yanda; Nopri Yanto; Sakral Hasby Puarada (Jurnal Mahasiswa Agribisnis, 2025)
This research was carried out in Blang Kolak II Village, Bebesen District, Central Aceh Regency. The research objective is to analyze consumer preferences and the financial feasibility of the Takengon Syalia home industry. Sampling was carried out using the accidental sampling method with 60 respondents. The data analysis methods used are qualitative and quantitative. The results of this research on consumer preferences show that the combination that consumers most consider when purchasing products athome industryTakengon Syaliais a coffee pie variant, large size, box packaging and price of IDR 30,000 with the most considered attributesnamely the variant attribute withNPR value (2,777), size attribute with NPR value (24,502), packaging attributes with NPR values (23,846) and the price attribute with the NPR value (21,875).